Destructive periodontitis, its prevalence among chronic periodontitis patients, with cohort incentive conditions (Mustansiria Dental Journal, 2018)
Sixty-six patients have been diagnosed and distinguished as having destructive periodentitis out of one thousand slowly growing chronic periodontitis (S.G.Ch.P.), constituted 6.6%, females was 68.18%, male was 31.81%, a significant difference was found between male and female.Possible activating and inverting factors was studied, restraint stress and depression appear having a significant relationship, nutritional factor as well showed a significant influence on inversion of S.G.Ch.P. into DP.High gingival index, sever bone destruction; deep packet and an eventual tooth mobility with generalized distribution pattern were the characteristic clinical feature of the disease.In conclusion local bacterial and systemic conditions either psychic or somatic may interfere in the activation and inversion of the adult periodentitis into destructive periodontitis under the basis of systemic and psychological factors .